2017
DOI: 10.2337/cd16-0007
|View full text |Cite
|
Sign up to set email alerts
|

Seeing the Person, Not the Illness: Promoting Diabetes Medication Adherence Through Patient-Centered Collaboration

Abstract: IN BRIEF Nonadherence to diabetes medications is a primary contributor to health complications and avoidable hospitalizations. This article discusses the evidence for taking a person-centered (as opposed to illness-centered) approach to promoting medication adherence among diabetes patients, provides suggestions for ways in which diabetes clinicians can best promote medication adherence, and argues for needed changes in how health care systems support providers in their efforts at adherence promotion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 54 publications
1
22
0
2
Order By: Relevance
“…Such accord between providers and patients around the initiation of insulin may provide a foundation for better persistence later on. [27][28][29][30][31][32][33][34] This process may also endow continuers with a sense of responsibility to better self-manage, find solutions for their own care, and to report fewer concerns and specific challenges after initiation. [35][36][37] Experienced or potential weight gain and hypoglycemia are among the top reported reasons to interrupt or discontinue treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Such accord between providers and patients around the initiation of insulin may provide a foundation for better persistence later on. [27][28][29][30][31][32][33][34] This process may also endow continuers with a sense of responsibility to better self-manage, find solutions for their own care, and to report fewer concerns and specific challenges after initiation. [35][36][37] Experienced or potential weight gain and hypoglycemia are among the top reported reasons to interrupt or discontinue treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Patient-centered care in diabetes involves evaluating individual patients’ unique characteristics, preferences, and abilities to devise a personalized treatment plan and therapeutic goals. Working to better understand patients’ experience with taking diabetes medications, improve the patient-provider relationship to gain patients’ trust, and obtain necessary health care system support for providers can promote adherence to the medication regimen in diabetes ( 10 ).…”
Section: Patient-centered Carementioning
confidence: 99%
“…[1,2,3] Improving medication management begins with an accurate exchange of information between the health care providers and the patients. [4,5] Therefore, new interventions are needed to move beyond these known barriers and help adherence. [5] Second, prior research has shown that individuals living with DM have low rate of compliance with lifestyle interventions.…”
Section: Introductionmentioning
confidence: 99%
“…[4,5] Therefore, new interventions are needed to move beyond these known barriers and help adherence. [5] Second, prior research has shown that individuals living with DM have low rate of compliance with lifestyle interventions. [6,7] Given that individuals with DM are more likely to have other risk factors, lifestyle intervention remains a crucial component of their care.…”
Section: Introductionmentioning
confidence: 99%